The effect of eight-week ladder-climbing exercise on the Atrial Natriuretic Peptide (ANP) gene expression in the heart tissue of Wistar male rats - majid azadmanesh; amir rashidlamir; seyed mahmoud hejazi (فصلنامه ابن سینا)
Background: The role of physical activity on blood pressure through its effect on Arterial Natriuretic Peptide (ANP) Gene has been previously approved. However, it is not clear what type of physical activity is more effective. The aim of this study was to investigate the effect of 8 weeks resistance training (ladder-climbing) on ANP gene expression in male Wistar rats. Materials and methods: The study was performed on male Wistar rats in control and resistance training groups. The exercise was climbing of a ladder with 85 degrees slope. Exercise intensity was controlled by increasing the weight and closing it to the rat tail. The heart tissue samples were collected and analyzed for ANP gene expression at 72 hours after the last training. Results: The results showed a significant difference between the two groups in ANP gene expression (p<0.05). The expression was higher in the heart tissue of training group compared to control group. Conclusion: The results of present study suggest that strength training with appropriate pattern and intensity can be a deterrent or control and management of hypertension. Probably the most important factor in resistance exercises is its effect on the structure and function of the heart, including ANP gene expression. Since the role of aerobic training was confirmed in previous studies, it is recommended that these two types of exercises be performed simultaneously.